Antimicrobial susceptibility of extended-spectrum beta-lactamase (esbl) producing Escherichia coli isolated from healthy residents of Nguyen Xa, Vu Thu, Thai Binh - Thang, Nguyen Nam; Hoa, Tran Thi; Hoa, Nguyen Thi; Diep, Khong Thi; Dung, Bui Huong; Quyen, Dong Van (Academia Journal of Biology, 2016)
The aim of this study was to evaluate antimicrobial susceptibility of ESBL-producing E. coli isolated from healthy residents of Nguyen Xa, Vu Thu, Thai Binh province. One hundred and sixty three E. coli isolates were examined for ESBL phenotype. Isolates with ESBL phenotype (n=135) were then evaluated for antimicrobial susceptibility to 12 antibiotics by disk diffusion method (CLSI, 2013). Antimicrobial susceptibility test results showed that ESBL-producing E. coli isolates were resistant to ampicillin, cefotaxime, tetracycline, trimethoprim-sulfamethoxazol with very high prevalence (70-100%); to streptomycin, nalidixic acid, chloramphenicol and gentamycin with high prevalence (30-70%); to ciprofloxacin, kanamycin and ceftazidime with lower prevalence of 23.7%, 21.5% and 18.5%, respectively. Only three antibiotics having resistant prevalence lower than 10% were meropanem, fosfomycin and cefoxitin. Classification under Magiorakos’ criteria showed that 87.4% ESBL-producing E. coli isolates were multidrug resistant (non-susceptible to three or more antibiotic catagories). The results indicated that ESBL-producing E. coli isolated from healthy residents of Nguyen Xa commune were resistant to a number of common antibiotics and 87.4% of them were multidrug resistant.   Citation: Nguyen Nam Thang, Tran Thi Hoa, Nguyen Thi Hoa, Khong Thi Diep, Bui Huong Dung, Dong Van Quyen, 2017. Antimicrobial susceptibility of extended-spectrum beta-lactamase (esbl) producing Escherichia coli isolated from healthy residents of Nguyen Xa, Vu Thu, Thai Binh. Tap chi Sinh hoc, 39(1): 95-100. DOI: 10.15625/0866-7160/v39n1.8395. *Corresponding author: nnthang_tmu@yahoo.com.vn. Received 10 June 2015, accepted 20 March 2017